Coping with psychiatric and psychological testimony - Faust, David (Oxford University Press)
"This book is designed to help attorneys differentiate expert testimony that is scientifically well-established from authoritative pronouncements that are mainly speculative. Building on the foundation of Jay Ziskin's classic work, this updated text blends the best of previous editions with discussion of positive scientific advances in the field to provide practical guidance for experts and lawyers. The authors summarize the state of the literature in numerous key areas of the behavioral sciences and law. Working from these foundations, the text provides guidance, tips, and strategies for improving the quality of legal evaluations and testimony, appraising the trustworthiness of experts' opinions, and as follows, bolstering or challenging conclusions in a compelling manner. Distinctive features of this text include detailed coverage of admissibility and Daubert challenges, with chapters written by a judge and attorney; hundreds of suggestions covering such topics as forensic evaluations, discovery, and the conduct of depositions and cross-examinations; and two chapters on the use of visuals to enhance communication and persuasiveness, including a chapter with over 125 model visuals for cases in psychology and law"--